A Study of Expressions of Politeness Strategies in Bẩck Obama s Greatest Speeches Introduced in the Book We are the change we seek: the speeches of Barack Obama. - Xa Thị Thu Hiền (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This research discovers politeness strategies used by Barack Obama – The former President of the United States of America - in his twenty-seven greatest speeches collected in the book ‘We Are the Change We Seek: The Speeches of Barack Obama’ by columnist E.J. Dionne and MSNBC host Joy-Ann Reid. On this study, the researcher analyzes Barack Obama’s utterances from the speeches which include politeness strategies to point out what kinds of politeness strategies that Mr. President used and discuss the significance of each strategy in every single situation. Finally, the tendency to use politeness strategies of Barack Obama is provided in the conclusion. This study was based on Brown and Levinson’s theory of politeness strategies. To carry out this study, the author chose qualitative and quantitative methods as analytical methods.